1991
DOI: 10.1177/036354659101900502
|View full text |Cite
|
Sign up to set email alerts
|

Anterior capsulolabral reconstruction of the shoulder in athletes in overhand sports

Abstract: From April 1, 1985, through June 30, 1987, 25 skilled athletes with shoulder pain secondary to anterior glenohumeral instability that had failed to improve with conservative therapy had an anterior capsulolabral reconstruction. All but one athlete completed a formal rehabilitation program with an average followup of 39 months. The results at followup were rated excellent in 68%, good in 24%, fair in 4%, and poor in 4%. Seventeen patients returned to their prior competitive level for at least 1 year. This opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
181
0
18

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(206 citation statements)
references
References 24 publications
7
181
0
18
Order By: Relevance
“…4,[7][8][9]18 In our current study, we examined the functional outcomes of 130 overhead athletes undergoing TACS at a mean follow-up of 29 months (range, 15-47 months). The results of our study indicate superior outcomes to those which reported using open and arthroscopic stabilization procedures without TACS, 3,12,15,17,20,[22][23][24]29 and similar to those of Savoie and Field, 25 Lyons et al, 16 and Levitz et al, 14 which used TACS. Eighty-eight percent of patients had good-to-excellent results, with 87% returning to the same level of competition at a mean of 8.4 months postoperatively.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…4,[7][8][9]18 In our current study, we examined the functional outcomes of 130 overhead athletes undergoing TACS at a mean follow-up of 29 months (range, 15-47 months). The results of our study indicate superior outcomes to those which reported using open and arthroscopic stabilization procedures without TACS, 3,12,15,17,20,[22][23][24]29 and similar to those of Savoie and Field, 25 Lyons et al, 16 and Levitz et al, 14 which used TACS. Eighty-eight percent of patients had good-to-excellent results, with 87% returning to the same level of competition at a mean of 8.4 months postoperatively.…”
Section: Discussionsupporting
confidence: 82%
“…3,12,15,17,20,[22][23][24]29 Open surgical stabilization procedures have resulted in range-ofmotion complications and a low return to competition. 3,12,15,17,[22][23][24]29 Early outcome reports using the Bristow procedure by Lombardo et al 15 report a mean 11°loss of shoulder external rotation with 0% of overhead athletes returning to play at a mean follow-up of 17 months, while Torg et al 29 report 16% of athletes returned to throwing at a mean follow-up of 47 months. Using the capsular shift procedure, Rubenstein et al 24 reported a mean 2°loss of shoulder external rotation with 46% of professional baseball pitchers having excellent results at a mean follow-up of 39 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main complications of any capsulolabral repair technique is loss of external rotation [16,34,45]. In previous series, loss of external rotation has ranged from 0°to 24° [16,27,44,45,47]. Early techniques of shoulder stabilization (ie, Bankart, Putti-Platt) used mediolateral retensioning, thus limiting external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The insufflations of the joint may have made the rotator cuff contact the superior glenoid at a higher angle than would occur physiologically when there is little fluid in the joint. However, a fluid pump has been used at the time of arthroscopy by others evaluating contact of the rotator cuff with the superior glenoid [7,15,17,18,24,35,37]. Second, it is possible making the measurements with the patients standing when awake and in the lateral position under anesthesia could have affected the results.…”
Section: Discussionmentioning
confidence: 99%